2022
DOI: 10.3389/fpsyg.2022.968109
|View full text |Cite
|
Sign up to set email alerts
|

Affective components in promoting physical activity: A randomized controlled trial of message framing

Abstract: Although the study of the affective components involved in predicting physical activity is spreading faster and faster, there is a lack of studies testing their role when promoting physical activity through message interventions. In the present study, we considered these components by focusing on how anticipated affective reactions and emotional processing of the messages influence receivers’ affective attitude toward physical activity, concurrent behavior, and future intention. A sample of 250 participants wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…In terms of participant characteristics, the DBN integrated the variables of the SEM model with additional variables that previous research has shown to play a role in predicting engagement in physical activity, namely the psychosocial variables envisaged in the Theory of Planned Behavior (i.e., attitude, perceived behavioral control, and social norm; Ajzen, 1991 ; Conner and Armitage, 1998 ; Wolstenholme et al, 2021 ; Carfora et al, 2022 ) and socio-demographic variables (i.e., age, education, and gender). Such a model would therefore provide an answer to the following research question.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In terms of participant characteristics, the DBN integrated the variables of the SEM model with additional variables that previous research has shown to play a role in predicting engagement in physical activity, namely the psychosocial variables envisaged in the Theory of Planned Behavior (i.e., attitude, perceived behavioral control, and social norm; Ajzen, 1991 ; Conner and Armitage, 1998 ; Wolstenholme et al, 2021 ; Carfora et al, 2022 ) and socio-demographic variables (i.e., age, education, and gender). Such a model would therefore provide an answer to the following research question.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Persuasive technology can also leverage cognitive biases such as the framing effect, which is the tendency of people to respond differently to information depending on how it is presented. For example, a fitness app might frame the benefits of exercising as "preventing disease" or "improving longevity" depending on the user's age and health concerns (Carfora et al, 2022;Weeks et al, 2022).…”
Section: Taxonomy Of Persuasion Techniquesmentioning
confidence: 99%
“…Attitude is made up of three essential components, which are related to (a) the cognitive component, which is based on the ideas and perceptions about the object of the attitude, (b) the affective component, characterized by the feelings that the person has and their intensity (acceptance-rejection), and (c) the behavioral component, given by the response that the subject has, in reaction to the object of the attitude ( Carfora et al, 2022 ). There are experiential referents, which creates predispositions or attitudes that affect the incorporation of the student into the learning process and affect their school achievement or failure ( Gómez Barbosa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%